Chemical analysis of the organic and inorganic fractions of rock art and pastes from Argentinian Septentrional Patagonian archaeological sites - María Teresa BOSCHÍN; Alicia Marta SELDES; Marta MAIER; Rodolfo M. CASAMIQUELA (Zephyrus, 2013)
We present the first results obtained in the chemical analysis of organic and inorganic components of rock art samples and paintings residues (pastes) obtained in archaeological excavations. The object of this research is to elucidate the work processes used and the knowledge that the aboriginal societies that lived in the central and occidental parts of the Argentinian Septentrional Patagonian had, between the XI and the final of XIX century. Our main interest is to know the recipes of the prehispanic workers and to determine the regional and/or chronological differences.